Isothermal Titration Calorimetry in Biocatalysis - Hagedoorn, Peter-Leon (Frontiers in Catalysis, 2022)
Isothermal titration calorimetry (ITC) is a popular chemical analysis technique that can be used to measure macromolecular interactions and chemical and physical processes. ITC involves the measurement of heat flow to and from a measurement cell after each injection during a titration experiment. ITC has been useful to measure the thermodynamics of macromolecular interactions such as protein-ligand or protein-protein binding affinity and also chemical processes such as enzyme catalyzed reactions. The use of ITC in biocatalysis has a number of advantages as ITC enables the measurement of enzyme kinetic parameters in a direct manner and, in principle, can be used for most enzymes and substrates. ITC approaches have been developed to measure reversible and irreversible enzyme inhibition, the effects of molecular crowding on enzyme activity, the activity of immobilized enzymes and the conversion of complex polymeric substrates. A disadvantage is that in order to obtain accurate kinetic parameters special care has to be taken in proper experimental design and data interpretation, which unfortunately is not always the case in reported studies. Furthermore, special caution is necessary when ITC experiments are performed that include solvents, reducing agents and may have side reaction. An important bottleneck in the use of calorimetry to measure enzyme activity is the relatively low throughput, but may be solved in the future by sensitive chip based microfluidic enzyme calorimetric devices.